PENGEMBANGAN VIDEO TRAINING BERBASIS VISME UNTUK MENINGKATKAN KOMPETENSI DIGITAL MARKETING DI LEMBAGA KURSUS ASAHAN SUMATERA UTARA - Hendrawan, Riki; Suryadi, Ahmad (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
The progress of a region is inextricably linked to the development of education within that region. The presence of digital marketing courses and training institutions contributes to regional development, and digital marketing is a key driver of business advancement. Digital marketing courses and training institutions continually strive to improve their learning to produce competent graduates. Participants' competency in digital marketing at the Ruang Kaji Akademi Course and Training Institute, located in Aek Ledong District, Asahan Regency, North Sumatra, was inadequate. Recognizing this issue, innovation in learning was deemed crucial. Therefore, researchers conducted a study on the development of a Visme-based video training program to enhance engaging digital marketing skills. This study employed the Research and Development method and the ADDIE development model, which has five steps: Analysis, Design, Development, Implementation, and Evaluation. The study also conducted an effectiveness test using the N-gein formula, resulting in an increase in the score of 0.76, categorized as highly effective, exceeding the standard effectiveness value of >0.56. These results indicate that the developed video training is effective for use in learning.